2018
DOI: 10.1096/fj.201800243rrr
|View full text |Cite
|
Sign up to set email alerts
|

circDiaph3 regulates rat vascular smooth muscle cell differentiation, proliferation, and migration

Abstract: Intimal hyperplasia is a reaction to vascular injury, which is the primary reason for vascular restenosis caused by the diagnostic or therapeutic procedure for cardiovascular diseases. Circular RNAs (circRNAs) are known to be associated with several cardiovascular conditions, but the expression of circRNAs in the neointima has not been reported in detail. In this study, we established the balloon‐injured rat carotid artery model and detected the expression of circRNAs in the carotid arteries with a microarray.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…For instance, a novel identified circRNA, circRNA_010567, regulates the fibrosis-associated protein resection in myocardial fibrosis diabetic db/db mice, demonstrating the circRNA_010567/miR-141/transforming growth factor β (TGF-β)1 axis in the diabetic mouse myocardial fibrosis model 21 . For other samples, references find that circDiaph3 knockdown increases the level of diaphanous-related formin-3 and promoted the differentiation of VSMCs to contractile type, and circDiaph3 promotes the Igf1r transcription and the proliferation and migration of VSMCs 22 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, a novel identified circRNA, circRNA_010567, regulates the fibrosis-associated protein resection in myocardial fibrosis diabetic db/db mice, demonstrating the circRNA_010567/miR-141/transforming growth factor β (TGF-β)1 axis in the diabetic mouse myocardial fibrosis model 21 . For other samples, references find that circDiaph3 knockdown increases the level of diaphanous-related formin-3 and promoted the differentiation of VSMCs to contractile type, and circDiaph3 promotes the Igf1r transcription and the proliferation and migration of VSMCs 22 …”
Section: Discussionmentioning
confidence: 99%
“…A series of studies from our group or other researchers has demonstrated that noncoding RNAs, including miRNAs (37)(38)(39)(40) and long noncoding RNAs (41,42) play vital roles in modulating the SC phenotype involved in peripheral nerve regeneration after injury. Emerging evidence has indicated impressive functions of circRNAs in both physiologic and pathologic conditions (43,44), especially in the nervous system and cancers (45,46). However, the role of circRNAs in peripheral nerve regeneration regulatory circRNAs involved in SC proliferation, which is of great importance to peripheral nerve regeneration, we screened differentially expressed circRNAs during sciatic nerve injury repair and focused on the role of a significantly down-regulated circRNAs circ-Ankib1 post-sciatic nerve injury and the underlying mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there were several researches on the effect of circRNAs on the proliferation, differentiation, and migration of myoblast. For example, in rat, rno-circ_005717 (circDiaph3) promoted vascular smooth muscle cells (VSMCs) differentiation by up-regulated diaphanous-related formin-3 (DIAPH3) and supported its proliferation and migration by up-regulated insulin, such as the growth factor 1 receptor ( IGF1R ) [17]. In mouse myoblast cell line-C2C12, circZfp609 (circular RNA, derived from Zinc Finger Protein 609) could repress the myogenic differentiation by sponge miR-194-5p to sequester its inhibition on the apoptosis regulator (BCL2) associated with transcription factor 1 ( BCLAF1 ) [18].…”
Section: Introductionmentioning
confidence: 99%